CREWS’ PERCEPTIONS OF MARITIME ENGLISH USAGE AT RORO BENGKALIS - Aprizawati Aprizawati; Aswandi Aswandi (INOVISH JOURNAL, 2018)
The objective of the research was to investigate crews’ perceptions of Maritime English Usage at RORO Bengkalis. This research was quantitative and qualitative research. The population in this study was crews at Roro Bengkalis. A set of questionnaire was distributed to 28 crews regarding their perceptions on oral communication usage during their voyage and a face to face interview was carried out to 6 crews. In this research, measurement of these statements using the Likert scale ranging from 1 = Strongly Disagree, 2 = Disagree, 3 = Undecided, 4 = Agree and 5 = Strongly Agree. The data collected was analyzed using SPSS 22 to know the normality, validity, and reliability of the instrument. The results of this study showed that crews had positive perceptions on English for Maritime usage during their voyage